THE EFFECT OF CAPITAL STRUCTURE, FIRM SIZE, GROWTH AND INVESTMENT OPPORTUNITY SET ON EARNINGS QUALITY - Harris Wibowo; Sufiyati Sufiyati (Graduate Program of Universitas Tarumanagara, 2026)
Amid an increasingly complex global economy, information transparency is a must for an efficient market. Financial statements provide a structured depiction of a company’s position, performance, and liquidity. Among these components, net income is commonly used as the primary measure of success and serves as the basis for investment, credit assessment, and valuation decisions. However, focusing solely on earnings entails risks because not all earnings are of equal quality. Earnings quality is defined to the degree that company profit reflects firms underlying financial ability and can predict future cash flows. Earnings quality has these qualities, which is reliability, relevance persistence, and minimal managerial intervention; conversely, low-quality earnings tend to be opportunistic, unstable, and misleading to decision makers. In this study, the quality of earnings in consumer non-cyclical enterprises listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period will be examined in relation to capital structure, firm size, growth, and investment opportunity set. The study employs a purposive sampling strategy based on preset criteria and a non-probability sampling technique. IBM SPSS was used to analyze the data. The findings show that while business size has a considerable beneficial impact on profits quality, growth and the investment opportunity set have no discernible negative effects, and capital structure has no discernible positive impact. These results give practitioners helpful information about important areas that can be strengthened to increase the quality of company earnings.